ANALISIS TINGKAT KEBERHASILAN ALUMNI JURUSAN MANAJEMEN TRANSPORTASI UDARA DAN MANAJEMEN BANDAR UDARA DALAM PERSAINGAN DUNIA KERJA ( STUDI KASUS: ALUMNI TAHUN 2017 DI SEKOLAH TINGGI PENERBANGAN AVIASI) - Sugiarti Sugiarti (JURNAL MITRA MANAJEMEN, 2020)
ABSTRACTThis research aims to explain the level of success of alumnus majoring in Air Transportation Management (MTU) and Airport Management (MBU) in the competitive world of work. The data obtained from graduates in 2017 amounted to 48 people consisting of 29 MTU graduates and 19 MBU graduates. The number of graduates in 2017 is 113 people. Based on the data obtained, classified based on the period of time and place of work obtained by graduates. For a period of time getting a job was first divided into three periods of less than three months, more than three months less than a year, and more than a year. Whereas the place of work obtained is classified into two, namely working in a field that is in accordance with the study program and working in a field that is not in accordance with the study program. The data obtained in the form of qualitative data so that the data analysis includes non-parametric statistics. The data distribution used is nominal and ordinal. In this non-parametric statistical method, it uses a comparation test with a Binomial Test and a correlation test with a Contingency Coefficient (Crosstabulation). Based on the results of the study obtained the first data analysis results with the Binomial Test : data in the Exact column. Sig (2-tailed) of 0.111, or significant> 0.05 (0.111> 0.05), then Ho is accepted, and Ha was rejected. This means that there is no relationship between the success of graduates who work in accordance with the study program. For the second data analysis, in the Chi-Square test table seen in the column Asymp. Sig is 0.993, or significance> 0.05, meaning Ho is accepted, and Ha was rejected. This means that there is no relationship between the study program and the period of time it gets a job. Keywords: success rate, majors, time period, place of work